The Soviet-Japanese Joint Declaration of 1956: a Difficult Path to Signing, a Difficult Fate after Ratification - A. N. Panov (Russian Japanology Review)
The article aims to study the process of formation and evolution of the territorial problem in the relations between the Soviet Union and Japan after the end of WWII up to the conclusion of the Soviet-Japanese Joint Declaration of 1956. Under consideration are the agreements of the Allied Powers over the postwar territorial limits of Japan. The author insists that the position of the U.S. towards the territorial provisions of the 1945 Yalta Agreements was repeatedly altered before and after signing the San Francisco Peace Treaty. Changes took place, on the one hand, because of the deterioration in the U.S. relations with the USSR, and, on the other hand, in correlation with Washington’s aim to “protect” itself from Tokyo’s demands to return Okinawa. It is noteworthy that Japan’s attitude to the problem of South Sakhalin and the Kuril Islands was from the very beginning not immutable either and has undergone multiple corrections. The paper gives a detailed examination of the process of the Soviet-Japanese negotiations on the normalization of bilateral relations in 1955-1956, providing an analysis of the reasons for the Soviet leadership’s readiness to hand over the Habomai islands and Shikotan to Japan. The author assesses the significance of the conclusion and the ratification of the Joint Declaration of 1956 for both the Soviet Union and Japan, as well as the attitude of both the Soviet/Russian leadership and the Japanese government to the possibility of the implementation of its territorial article. After Prime Minister Abe had stated in November 2018 that the Japanese side is ready to hold negotiations on the basis of the territorial article of the 1956 Joint Declaration, Russo-Japanese negotiations on the conclusion of the Peace Treaty were launched. However, compared to the Japanese side, for which the pivotal aim is to fix an agreement on the ownership of the islands and the borderline, much more important in the Russian motivation is to acquire Japan’s recognition of the legality of the Russian possession of the Kuril Islands, to obtain guarantees that the Japan-U.S. security alliance would not be aimed against Russia’s interests, as well as to lay a base for a broader development of bilateral relations with Japan. Against the background of the unwillingness of the public opinion of the two countries to accept the 1956 Declaration as a base for resolving the territorial problem, the possibility to achieve a Peace Treaty in the forseeable future is seen as unrealistic.